Supporting the Inclusion of Socially Vulnerable Early Adolescents: Theory and Illustrations of the BASE Model - Farmer, Thomas W.; Sterrett, Brittany I.; Norwalk, Kate E.; Chen, Chen-Chih; Dawes, Molly; Hamm, Jill V.; Lee, David L.; Farmer, Adaline G. (Frontiers in Education, 2021)
We focus on the inclusion of socially vulnerable early adolescents including students with special education needs (SEN). Building from multiple intervention and randomized control trials of a professional development model aimed at supporting teachers’ management of the classroom social context, we provide an overview of the Behavioral, Academic, and Social Engagement (BASE) Model as a framework to foster social inclusion. We briefly review the conceptual foundations of this model and we present the delivery (i.e., directed consultation, the scouting report process) and content (i.e., Academic Engagement Enhancement, Competence Enhancement Behavior Management, Social Dynamics Management) components of BASE. We then briefly discuss the intervention support needs of subtypes of socially vulnerable youth and how these needs can be differentially addressed within the BASE framework.